Layanan Ekosistem Kumbang pada Tata Guna Lahan Talun Campuran di Lanskap Cijedil, Cianjur - Vina Rizkawati (LPPM Universitas Negeri Jakarta, 2021)
This research aimed to know the diversity of beetles in mixed orchard and its relation to the ecosystem services provided. Sampling method used were pitfall trap and hand collecting. Pitfall trap was placed every 50 meter through 450-meter-long walked line transect and checked after 24 hours. Three variations of bait used for pitfall were apple cedar vinegar, cattle faeces, and white lab rat’s carrion. Samples collected were then preserved and identified in the laboratory. Supporting data such as abiotic and biotic parameters were recorded on each sampling point. Data was analyzed using relative frequency, relative abundance, dominance, diversity index, and evenness index. Total of 268 beetles were collected, representing 44 species that belong to 15 families. Mixed orchard has a diversity index (H') of 2.460 and evenness index (J') of 0.755. The most abundant species found on mixed orchard was Onthophagus discedens, a generalist beetle which is decomposer mainly found on carrion and animal waste bait. Based on feeding guild structure, mixed orchard inhabited by saprophaga, coprophagous, fungivore, xylophaga, herbivore, predator.